2012
DOI: 10.1007/s00404-012-2625-7
|View full text |Cite
|
Sign up to set email alerts
|

Rudimentary horn pregnancy: a 10-year experience and review of literature

Abstract: The review presents the existing imaging criteria to diagnose rudimentary horn pregnancy and suggests future research to enhance the limited evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 28 publications
1
54
0
4
Order By: Relevance
“…present decade, owing to improvements in healthcare and diagnostic facilities. 7 However, Jain et al reported that the fetal salvage rate is still only 2%. 2 Common diagnostic modalities include hysterosalpingography, combined laparoscopy and hysteroscopy, ultrasonography (preferably three-dimensional) and MRI.…”
Section: Resultsmentioning
confidence: 99%
“…present decade, owing to improvements in healthcare and diagnostic facilities. 7 However, Jain et al reported that the fetal salvage rate is still only 2%. 2 Common diagnostic modalities include hysterosalpingography, combined laparoscopy and hysteroscopy, ultrasonography (preferably three-dimensional) and MRI.…”
Section: Resultsmentioning
confidence: 99%
“…Своевременная диагностика порока позволяет разработать алгоритм ведения таких больных, вы-полнить хирургическую коррекцию аномалии разви-тия и в перспективе предотвратить возможность бе-ременности в рудиментарном роге, которая, по дан-ным литературы [14], приводит к разрыву рога в 80-90% случаев.…”
Section: заключениеunclassified
“…Чем толще миометрий и лучше его кровоснаб-жение, тем развивается, как правило, более массив-ное внутрибрюшное кровотечение с клиникой «острого» живота и геморрагического шока, которое может привести к летальному исходу больной [12]. По данным литературы [12,14,15], отмечено сниже-ние материнской смертности при разрыве рудимен-тарного рога с 18,0% в XIX веке до 0,5% в наши дни, это связано, несомненно, с усовершенствованием методов диагностики, что помогает в ранние сроки определить оптимальную тактику ведения такой группы пациенток. Однако по-прежнему остается высоким риск таких осложнений, как: врастание плаценты (placenta increta), разрыв рудиментарного рога, массивное внутрибрюшное кровотечение с не-обходимостью переливания крови.…”
unclassified
See 2 more Smart Citations